2021
DOI: 10.3389/fimmu.2021.697026
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine in Cancer Immunotherapy: An Undervalued Therapeutic Target

Abstract: N6-methylation of adenosine (m6A), a post-transcriptional regulatory mechanism, is the most abundant nucleotide modification in almost all types of RNAs. The biological function of m6A in regulating the expression of oncogenes or tumor suppressor genes has been widely investigated in various cancers. However, recent studies have addressed a new role of m6A modification in the anti-tumor immune response. By modulating the fate of targeted RNA, m6A affects tumor-associated immune cell activation and infiltration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 128 publications
(197 reference statements)
1
15
0
Order By: Relevance
“…Moreover, tumor-associated macrophages are closely associated with the clinical benefit of anti-PD-1 treatment ( Voss et al, 2018 ). Importantly, different m6A modification patterns have been proposed to predict immunotherapy efficacy in pan-cancers ( Quan et al, 2021 ), here, we demonstrated the notable correlations between the m6A score and TME immune infiltration landscapes, immune checkpoint expression levels, distinct IPS, and sensitivity to TKIs, uncovering the potential usefulness of the m6A score in assessing the response to ICIs in ccRCC. Nevertheless, these results can not signify a causal correlation between m6A score and immunotherapy response in ccRCC, and we ought to gather more clinical data in future studies to validate the correlations.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, tumor-associated macrophages are closely associated with the clinical benefit of anti-PD-1 treatment ( Voss et al, 2018 ). Importantly, different m6A modification patterns have been proposed to predict immunotherapy efficacy in pan-cancers ( Quan et al, 2021 ), here, we demonstrated the notable correlations between the m6A score and TME immune infiltration landscapes, immune checkpoint expression levels, distinct IPS, and sensitivity to TKIs, uncovering the potential usefulness of the m6A score in assessing the response to ICIs in ccRCC. Nevertheless, these results can not signify a causal correlation between m6A score and immunotherapy response in ccRCC, and we ought to gather more clinical data in future studies to validate the correlations.…”
Section: Discussionsupporting
confidence: 55%
“…Among all cancer-related RNA modifications, m 6 A is the most important one. m 6 A is methylation at the N 6 position of the adenine of RNA and is widely documented to regulate the expressions of many oncogenes or tumor suppressor genes to affect the pathological characteristics of various tumor cells or tumor microenvironments [17,18]. M 5 C is methylation at position 5 of cytidine residues, which are abundant on DNA, mRNA, and ncRNAs [19].…”
Section: Discussionmentioning
confidence: 99%
“…As a dynamic and reversible methyl-modification, increasing evidences indicated the closely connection between M6A and immune infiltration characterization in various cancers, including GC [ 42 , 43 ]. M6A modification is mainly regulated by its related genes, which can be classified into readers, writers, and erasers.…”
Section: Discussionmentioning
confidence: 99%